Effect of pilates exercise versus yoga on primary dysmenorrhea in adolescent girls - El Nahas, Engy M.; Tammam Atia, Doaa; Hassan, Mai H.; Abd El-Hakim, Ahmed Abd El-Moneim; Sae’d Mahmoud, Sally Mohamed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to investigate the effect of Pilates exercise versus yoga on primary dysmenorrhea in adolescent girls. The study was designed as a randomized controlled trial and was conducted with adolescent girls at an experimental school in Cairo. Sixty adolescent girls, aged 12 to 16 years, who were all diagnosed with primary dysmenorrhea, participated in this study. They were randomly assigned to one of two groups: Group (A) (Pilates exercise) with 30 participants, and Group (B) (Yoga exercise) with 30 participants. Participants were assessed before and after the treatment period. Group (A) performed Pilates exercises for 30 minutes, three days per week, for three months, while Group (B) engaged in yoga exercises for 30 minutes, three days per week, for three months. The Visual Analog Scale (VAS) was used to rate the intensity of pain, and the Verbal Multidimensional Scoring System (VMS) was used to assess the severity of menstrual symptoms. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS). The study revealed a statistically significant improvement in VAS and VMS measures following Pilates exercise in Group A (p < 0.05). Similarly, a statistically significant improvement in VAS and VMS measures was observed following yoga exercise in Group B (p < 0.05). Both Pilates and yoga exercises demonstrated a significant impact on managing primary dysmenorrhea. The findings indicate that these mind-body interventions are effective in alleviating the severity of menstrual pain and related symptoms.